Fire automation in the life cycle of a building – methods of verification, issues with system upgrade - Węgrzyński, Wojciech; Antosiewicz, Piotr; Krajewski, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
This article presents the issues with the marketing of construction products that are part of fire automation of a building. The issues in marketing of the newest solutions are localised already within the testing process and the slow process of updating current standards. Also mounting the construction product bring new challenges – authors present a method of hot smoke testing, that allows for a quick and reliable assesment of system cooperation, also in the life of the building.